2022
DOI: 10.1002/cam4.5310
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin‐induced HSF1‐HSP90 axis enhances the expression of functional PD‐L1 in oral squamous cell carcinoma

Abstract: Head and neck cancer is the sixth most commonly diagnosed cancer worldwide, and oral cancer is the most frequent tumor of the head and neck region. More than 90% of oral cancer is classified as oral squamous cell carcinoma (OSCC), with 377,713 new cases and 177,757 deaths worldwide in 2020. 1,2 Together with surgery, chemotherapy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Our data also suggested that tumors' stress levels differed among clinical cases (Figures 4,5). Tumor cells are characteristically exposed to various stresses from the microenvironment, such as immune/inflammatory stress [19], therapeutics [18], hypoxia [22,[52][53][54][55], acidification [56,57], hyperthermia [58,59] or heat stress [4,6,19,25,28], endoplasmic reticulum stress [60], nuclear envelope stress [61,62], replication stress [63], oxidative stress [64], mechanical stress, osmotic stress, genotoxic (DNA damage) [65,66] and proteotoxic stress [1,2,4,67]. Therefore, it might be difficult to determine the types and levels of stresses in each tumor.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Our data also suggested that tumors' stress levels differed among clinical cases (Figures 4,5). Tumor cells are characteristically exposed to various stresses from the microenvironment, such as immune/inflammatory stress [19], therapeutics [18], hypoxia [22,[52][53][54][55], acidification [56,57], hyperthermia [58,59] or heat stress [4,6,19,25,28], endoplasmic reticulum stress [60], nuclear envelope stress [61,62], replication stress [63], oxidative stress [64], mechanical stress, osmotic stress, genotoxic (DNA damage) [65,66] and proteotoxic stress [1,2,4,67]. Therefore, it might be difficult to determine the types and levels of stresses in each tumor.…”
Section: Discussionmentioning
confidence: 54%
“…MDPI and/or the editor(s) disclaim responsibility for any injury to people or property resulting from any ideas, methods, instructions, or products referred to in the content. observed in many cancer types and correlates with poor prognosis, increased metastatic potential and resistance to therapy [16][17][18][19]. Moreover, the HSP90 alpha and beta isoforms are often released with extracellular vesicles (EV), including exosomes, by cancer cells and can thus trigger cancer initiation and progression, as well as the polarization of tumorassociated macrophages to an immunosuppressive M2 subtype [6,17,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Our data also suggested that tumors’ stress levels differs among clinical cases ( Figure 7 ). Tumor cells are characteristically exposed to various stresses from the microenvironment, such as immune/inflammatory stress [ 19 ], therapeutics [ 18 ], hypoxia [ 22 , 58 , 59 , 60 , 61 ], acidification [ 62 , 63 ], hyperthermia [ 64 , 65 ] or heat stress [ 4 , 6 , 19 , 25 , 28 ], endoplasmic reticulum stress [ 66 ], nuclear envelope stress [ 67 , 68 ], replication stress [ 69 ], oxidative stress [ 70 ], mechanical stress, osmotic stress, and genotoxic (DNA damage) [ 71 , 72 ] and proteotoxic stress [ 1 , 2 , 4 , 73 ]. Therefore, it might be difficult to determine the types and levels of stresses in each tumor.…”
Section: Discussionmentioning
confidence: 99%
“…As HSP90 has several hundred protein substrates (called ‘clients’), it is involved in many cellular processes beyond protein folding, which include DNA repair, development, the immune response, and neurodegeneration [ 11 , 12 , 13 , 14 , 15 ]. Elevated expression of HSP90 has been observed in many cancer types and correlates with poor prognosis, increased metastatic potential, and resistance to therapy [ 16 , 17 , 18 , 19 ]. Moreover, the HSP90 alpha and beta isoforms are often released with extracellular vesicles (EV), including exosomes, by cancer cells and trigger cancer initiation and progression, as well as the polarization of tumor-associated macrophages (TAM) to an immunosuppressive M2 subtype [ 6 , 17 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, studies are underway to test whether inhibition of HSF1 with small molecular inhibitors, such as DTHIB (74), can result in the same influx of CD8+ T cells, which could prime the targeting of HSF1 as a potential clinical approach to making breast cancer cells more immune cell-rich. Lastly, the role of HSF1 in CD8+ T cell activity or exhaustion warrants further investigation considering HSF1 has been reported to upregulate PD-L1 expression on cancer cells (75,76). These results generate several new lines of investigation for the role of HSF1 in new aspects of tumor biology and tumor-immune interactions.…”
Section: Discussionmentioning
confidence: 99%